Need Analysis of English Speaking Skills for Local Guides in Tete Batu: An ESP Design - Setiawan, Budi; Marzuki, M. Junaidi; Suherman, Andri; Husnu, Muhammad (JELITA, 2025)
This study aims to shed light on the specific English-speaking needs of local guides in Tete Batu by exploring the relevant learning topics for their guiding roles and examining the challenges they face in delivering effective services to tourists. This research used a sequential explanatory mixed-method design. In the first phase, questionnaires were distributed to 27 active local guides to identify the most frequently used English topics in their guiding activities. The data were analyzed using descriptive statistics with SPSS 26.00 to determine topic priorities. In the second phase, semi-structured interviews were conducted with five selected guides to gain deeper insights into the challenges they face and to confirm the questionnaire results. The interview data were analyzed using thematic analysis by Braun and Clarke (2006). The findings revealed that a total of 22 English learning topics are used by local guides in Tete Batu. Among these, 11 topics are frequently used in daily guiding practices, while the other 11 are applied only in specific or situational contexts. In addition, the guides reported several challenges in their work, such as sudden weather changes, limited destination knowledge among new guides, tourists’ entrance tickets, the absence of a Tourist Information Center (TIC), and the lack of learning resources.The findings suggest that English training should focus on practical, topic-based content aligned with real guiding tasks.